Kepastian Hukum terhadap Keabsahan Peralihan Tanah yang Belum Bersertipikat - Krestianto, Agustinus Herry; Abadi, Suwarno (Universitas Muhammadiyah Ponorogo, 2025)
Law Number 5 of 1960 concerning Basic Agrarian Principles Regulations confirms that there is not an inch of land in our country that does not have an owner or is called